Sociodemographic and Lifestyle Determinants of Adherence to Current Dietary Recommendations and Diet Quality in Middle-Aged Spanish Premenopausal Women - Alonso-Cabezas, Marina; Pollán, Marina; Alonso-Ledesma, Isabel; Fernández de Larrea-Baz, Nerea; Lucas, Pilar; Sierra, Ángeles; Castelló, Adela; Pino, Marina Nieves; Pérez-Gómez, Beatriz; Martínez-Cortés, Mercedes; Lope, Virginia; Ruiz-Moreno, Emma (Frontiers in Nutrition, 2022)
Background A healthy diet when approaching menopause could prevent some of the symptoms associated with the climacteric. Few studies examine adherence to current healthy dietary recommendations in middle-aged premenopausal women. Our objective was to analyze the diet quality and the adherence to the Spanish Society of Community Nutrition (SENC) dietary recommendations in middle-aged Spanish premenopausal women, and to identify the associated sociodemographic and lifestyle factors. Methods This is a cross-sectional study based on 1251 premenopausal women, aged 39–50, who attended to Madrid City Council Medical Diagnostic Center. Women completed an epidemiological and a food frequency questionnaire. Degree of adherence to the SENC recommendations was estimated with a score that evaluated null (0 points) and full (1 point) adherence of each specific recommendation. Associations were explored using an ordinal logistic multivariable regression model. Results Regarding food groups, the worst adherence was found for sweets, red/processed meat, olive oil and eggs. Most of the participants exceeded the recommended caloric intake from proteins and fats, and practically all of them showed vitamin D intake deficiency. The overall score ranged from 2 to 12 (out of 15), with a median of 6.0 (interquartile range: 5.0–7.0). Former smokers (OR: 1.38; 95%CI: 1.08–1.78), as well as those with higher educational level (ORSSecondary:1.68; 95%CI: 0.97–2.93, ORUniversity:1.82; 95%IC: 1.05–3.14), with two or more children (OR: 1.31; 95%IC: 1.00-1.72), with higher caloric intake (OR>2188.2kcal/day: 8.22; 95%CI: 6.19–10.92) and with greater physical activity (OR≥21METS−h/week: 1.29; 95%CI: 0.95-1.76) showed greater adherence. Conclusions Almost two-thirds of middle-aged premenopausal participants showed low or moderate compliance with SENC recommendations. Education, smoking, parity, and physical activity were associated with the degree of adherence to these recommendations.